2012
DOI: 10.4103/0019-557x.99913
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the lunar cycle on frequency of births: A retrospective observational study in Indian population

Abstract: For ancient period moon has been held responsible for many biological activities. That way, lunar cycle, by activity of moon, has been held responsible for increase in number of child birth. In this retrospective, observational study, we examined a total of 9890 full-term spontaneous deliveries as well as non-elective cesarean sections that occurred throughout 12 lunar months (February 7 th , 2008-January 25 th , 2009) in a rural medical college to evaluate the influence of the lunar position on the distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
1
6
0
5
Order By: Relevance
“…On the other hand, a study by Abell and Greenspan, 19 on 11691 deliveries in 51 lunar cycles, shows no correlation between birth rate and the phases of the Moon. Data provided by other Authors, 20 with a cohort study of the same amount, has not recorded statistically significant differences in the frequency of deliveries during the various phases of the lunar cycle, regardless of the type of delivery. Data provided by Joshi et al, 21 Periti et al 22 and Romero Martinez et al 23 seems to be conclusive: they showed that there was no statistically significant difference between the frequency of the deliveries during full Moon days compared to other days, concluding that the analysis of the evidence provided does not support the theory which states that the full Moon phase is related to an increase in the frequency of the deliveries.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…On the other hand, a study by Abell and Greenspan, 19 on 11691 deliveries in 51 lunar cycles, shows no correlation between birth rate and the phases of the Moon. Data provided by other Authors, 20 with a cohort study of the same amount, has not recorded statistically significant differences in the frequency of deliveries during the various phases of the lunar cycle, regardless of the type of delivery. Data provided by Joshi et al, 21 Periti et al 22 and Romero Martinez et al 23 seems to be conclusive: they showed that there was no statistically significant difference between the frequency of the deliveries during full Moon days compared to other days, concluding that the analysis of the evidence provided does not support the theory which states that the full Moon phase is related to an increase in the frequency of the deliveries.…”
Section: Discussionmentioning
confidence: 74%
“…Our data do not find agreement with the weekly rhythm, nor with the annual rhythm or with the Synodic lunar month as defined in the study of Guillon et al, 16 considered the largest sample size for study (5927978 cases) and span (6 years); on the contrary, our conclusions agree with those given by numerous other studies found in literature. [19][20][21][22][23]…”
Section: Discussionmentioning
confidence: 99%
“…In human, relationship of obstetric delivery with lunar cycle has been studied and discussed. Although some studies showed a positive association [2,15], most of the studies demonstrated no association between them [3,1621]. Recently, Marco-Gracia performed a retrospective cohort analysis on 23,689 spontaneous deliveries within the home for 1484 lunar cycles between the years 1810 and 1929 in rural Spanish villages.…”
Section: Discussionmentioning
confidence: 99%
“…In human, an increase on the percentage of deliveries in the full moon and the waning gibbous phases was found [2]. On the contrary, no difference was observed in the frequency of child births during various phase of lunar cycle [3]. A different analysis also demonstrated that there was no predictable influence of the lunar phases on the frequency of child births [4].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, there are some scientific studies with contradictory results. In a study involving almost 10 000 deliveries in India, a relationship between lunar cycle and the frequency of deliveries was not found (Bharati et al, 2012). Similarly, a study conducted in Germany involving over 6000 gestations did not find a correlation between lunar phase and frequency of delivery (Staboulidou et al, 2008).…”
Section: Introductionmentioning
confidence: 93%